Does Income Inequality Lead to Consumption Inequality? Evidence and Theory1 - KRUEGER, DIRK; PERRI, FABRIZIO (Review of Economic Studies, 2006)
Using data from the Consumer Expenditure Survey, we first document that the recent increase in income inequality in the U.S. has not been accompanied by a corresponding rise in consumption inequality. Much of this divergence is due to different trends in within-group inequality, which has increased significantly for income, but little for consumption. We then develop a simple framework that allows us to characterize analytically how within-group income inequality affects consumption inequality in a world in which agents can trade a full set of contingent consumption claims, subject to endogenous constraints emanating from the limited enforcement of intertemporal contracts. Finally, we quantitatively evaluate, in the context of a calibrated general equilibrium production economy, whether this set-up, or alternatively a standard incomplete markets model, can account for the documented stylized consumption inequality facts from the U.S. data.